IgA vasculitis (formerly Henoch-Schönlein purpura) in an adult with systemic lupus erythematosus. (9th September 2015) - Bernardino, Vera; Mendes-Bastos, Pedro; Rodrigues, Ana; Riso, Nuno
Abstract : We report a case of a 65-year-old man with systemic lupus erythematosus (SLE) and antiphospholipid syndrome, presenting palpable purpuric lesions, necrotic blisters and swelling ankles, after a previous tracheobronchitis episode. Laboratory data were remarkable for mild proteinuria and imaging studies were normal. A skin biopsy showed IgA deposits on superficial dermal capillaries and IgA vasculitis (IgAV) (former Henoch-Schönlein purpura) was assumed. The patient was treated with colchicine, deflazacort and azathioprine, but as a regression in the purpuric lesions was noted, a decline in renal function was detected. A kidney biopsy revealed mesangial proliferation with IgA deposition and IgAV nephritis was considered. Immunosuppressive treatment was adjusted, with progressive normalisation of renal function and disappearance of proteinuria over a monthly follow-up; after 6 months, total remission was achieved. To the best of our knowledge, this is the first reported case of IgAV in an adult patient with SLE.